Colour Term lexemes as Reproduction of Dmytro Dontsov’s Ideology (Linguostylistic Studies, 2016)
The article examines and discusses colouristic vocabulary as one of the most powerful means of reproducing national component of the language, as the representative element of the verbal picture of the world and unique marker-reproducer of the author`s individual style. The words with the colour seme reproduce Ukrainian-centric, strongly motivated views of Dmytro Dontsov. The paper illustrates the contrast between two ideologies: national and liberal. National background of the text is reproduced by such lexemes of colour terms as black (black earth, black locust), red (red gimp) and gold (golden saddle, to touch the gold), since it concerns the heroic past of the Ukrainian nation, the might and greatness of the Hetmanship and the period of Cossacks. Liberal values ​​(according to the text of the publicist) are tranquility, peace and calmness, peaceful work and contemplation of beauty, and accordingly such lexemes as blue, green, white (river, sun, grass, periwinkle) are used to reproduce those values.Colour lexemes in the book «The Spirit of Our Past» are mostly used with additional semantic loading. The author lays emphasis on the Dontsov’s preferences to using such stylistic devices as antithesis, epithets, metaphors and metonymies, and states that using tautology Dontsov intensifies the colour characteristics of the text and the world around.Key words: lexeme of colour, individual author's ideology, basic values, additional semantic loading. References